Understanding the interaction of resin composite with light for predictable aesthetic results in anterior teeth: A case report - Scotti, Cassiana Koch; Bastos, Natália Almeida; Velo, Marília Matar de Amoêdo Campos; Zabeu, Giovanna Speranza; Bueno, Lígia Saraiva; Bombonatti, Juliana Fraga Soares; Mondelli, Rafael Francisco Lia (Brazilian Dental Science, 2018)
This case report illustrates a conservative technique for reintervention on anterior composite restorations in a young patient with composite veneers. The treatment incorporated the use of photos and digital planning to establish a harmonious smile design. In order to conserve the dental tissues, existing resin composites restorations in maxillary anterior teeth were carefully removed to minimize enamel reduction, followed by a study of color and shade of teeth considering factors such as hue, chroma, luminosity, opacity, translucency and light effects. Eight direct veneers were built up with resin composite taking the optical properties of the material into account and their influence on the thickness of the layers that create specific light effects when superimposed on each other. To obtain excellent results with a predictable working protocol, nanohybrid composite systems facilitate good aesthetics, avoiding more invasive treatment in an economic manner. Keywords Dental aesthetic; Optical proprieties; Resin composite.